2011
DOI: 10.1016/j.jval.2010.10.011
|View full text |Cite
|
Sign up to set email alerts
|

The cost-utility analysis of adult male circumcision for prevention of heterosexual acquisition of HIV in men in sub-Saharan Africa: a probabilistic decision model

Abstract: AMC is found to be cost saving. AMC may be seen as a promising new form of strategy for prevention of heterosexual acquisition of HIV in men, but should never replace other known methods of HIV prevention and should always be considered as part of a comprehensive HIV prevention package.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…For conditions with multiple published DWs, preference was first given to the values from GBD 2013 study,[8] followed by the GBD 2004 update,[7] and then Poenaru et al[20] For conditions without a DW from those sources, values published from other sources were used. b Calculated assuming circumcision intervention reduces HIV prevalence from 12% to 6% [21] with an average of 15.5 DALY/case of HIV averted [22] using the universal life expectancy of a 0 year old male with 3% discounting and age-weighting.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For conditions with multiple published DWs, preference was first given to the values from GBD 2013 study,[8] followed by the GBD 2004 update,[7] and then Poenaru et al[20] For conditions without a DW from those sources, values published from other sources were used. b Calculated assuming circumcision intervention reduces HIV prevalence from 12% to 6% [21] with an average of 15.5 DALY/case of HIV averted [22] using the universal life expectancy of a 0 year old male with 3% discounting and age-weighting.…”
Section: Resultsmentioning
confidence: 99%
“… b Calculated assuming circumcision intervention reduces HIV prevalence from 12% to 6% [21] with an average of 15.5 DALY/case of HIV averted [22] using the universal life expectancy of a 0 year old male with 3% discounting and age-weighting.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a longterm follow up to the large-scale MC trial in Uganda (Gray et al, 2007), HIV incidence was 73% lower in trial participants who had accepted MC than in those who had declined, and 67% lower in control-group participants who accepted MC after trial closure than in those who declined . Two meta-analyses (Byakika-Tusiime, 2008;Mills, Cooper, Anema, & Guyatt, 2008), a systematic review (Siegfried, Muller, Deeks, & Volmink, 2009), and a cost analysis (Uthman, Popoola, Yahaya, & Aremu, 2011) have confirmed that HIV risk can be substantially reduced through MC. The World Health Organization (WHO) and the United Nations Programme on HIV/ AIDS (UNAIDS) (2007) recommend that voluntary adult MC be considered as an option within a comprehensive prevention program in countries where HIV prevalence is epidemic and transmission is predominantly heterosexual.…”
Section: Male Circumcision To Reduce Hiv Transmissionmentioning
confidence: 90%
“…A wet penis may enhance attachment of infectious virions for longer, reduce healing after trauma, or may lead to balanitis under the foreskin and consequent micro-ulcerations (O'Farrell et al, 2006). In high HIV prevalence settings, MC has been shown to be cost-effective for prevention of this virus (Williams et al, 2006;Uthman et al, 2011). In sub-Saharan Africa the cost of MC is always lower than the cost of anti-retroviral treatment; by how much depends on the method of circumcision used.…”
Section: Male Circumcision For Hiv Preventionmentioning
confidence: 99%